2012
DOI: 10.1007/s10396-012-0345-z
|View full text |Cite
|
Sign up to set email alerts
|

Impact of transcatheter closure of atrial septal defects on cardiac function

Abstract: Atrial septal defect closure decreased EF on the surface, thereby maintaining the same stroke volume and cardiac output. Patients with diastolic dysfunction before closure might have a higher risk of developing congestive heart failure after ASD closure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 25 publications
1
3
1
Order By: Relevance
“…In the current study, LV volume and EF were measured sequentially, and diastolic and systolic LV volume increased while EF did not change in any of the groups. These results were in agreement with those of previous studies [14,16], including our own, which reported that LV size was increased 1 day after ASD closure [12]. Following device closure, the left-to-right shunt was abolished and LV filling improved, resulting in an increase in LV dimension.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In the current study, LV volume and EF were measured sequentially, and diastolic and systolic LV volume increased while EF did not change in any of the groups. These results were in agreement with those of previous studies [14,16], including our own, which reported that LV size was increased 1 day after ASD closure [12]. Following device closure, the left-to-right shunt was abolished and LV filling improved, resulting in an increase in LV dimension.…”
Section: Discussionsupporting
confidence: 93%
“…Doppler indices concerning diastolic function were poorest in older patients, and even though all Doppler indices changed in the same direction with time after ASD closure in all age groups, the age-dependent differences persisted. In our previous study, we showed that deceleration time, e 0 , and E/e 0 were worse at 1 day after ASD closure [12]. In the current study, however, deceleration time increased 1 day after ASD closure, e 0 decreased, and E/e 0 increased significantly over time but E/A did not change.…”
Section: Discussioncontrasting
confidence: 69%
“…28 Tashiro also noted that although both E/A and E/E′ increased, it was only significant in the latter. 24 Aslan et al reported that E/A increase was significant in their study and suggested that this immediate increase in the mitral inflow E-wave and LA conduit function could result from the passage of all blood in the LA to the LV in the early diastole and the diminished pressure exerted on LV by the diastolic RV volume overload. 25 Another important observation was a significant decrease in RVSP after the procedure.…”
Section: Discussionmentioning
confidence: 86%
“…23 Tashiro et al reported that 1 day after closure LVEF decreased significantly and suggested it could be due to evaluating the changes using 3D echocardiography. 24 In another study by Aslan et al, LVEDD improved almost after 1 day, LVESD did not change significantly even after 6 months and LVEF improved significantly only after 6 months. 25 In addition, Vijayvergiva et al noted there was no significant change in LVEF as assessed by echocardiography ( P = 0.132) and radionuclide scan ( P = 0.143).…”
Section: Discussionmentioning
confidence: 89%
“…The early diastolic velocity of the mitral annulus (Ea) obtained by tissue Doppler imaging (TDI) has been reported to be a preload-independent index for evaluating LV diastolic function in patients with heart disease and correlates inversely with the time constant (tau) of LV isovolumic relaxation [5][6][7]. When TDI is combined with pulsed-Doppler measurement of transmitral velocity in early diastole (E), the resultant E/Ea ratio correlates with invasively measured LV filling pressures [6,[8][9][10][11].…”
Section: Introductionmentioning
confidence: 98%